An interfacially polymerized self-healing organo/hydro copolymer with shape memory. Issue 14 (26th March 2019) - Wang, Binshuai; Zhai, Wenzhong; Fan, Jun-Bing; Xu, Jun; Zhao, Wenpeng; Feng, Xianqi
Abstract : An interfacially polymerized organo/hydro copolymer with rapid self-healing and shape memory was demonstrated. Abstract : Organo/hydro copolymer materials have recently received significant attention in the fields of energy, environment and healthcare. Herein, we report the fabrication of a robust organo/hydro copolymer with rapid self-healing and shape memory by emulsion interfacial polymerization. The emulsion interfacial polymerization allowed the formation of a crosslinked organo/hydro copolymer with hydrogen-bonded networks, significantly enhancing the mechanical properties; the proposed organo/hydro copolymer substantially outperformed most of the synthetic self-healing polymers based on hydrogen bonding interactions. We showed that the interfacially polymerized organo/hydro copolymer exhibited good self-healing capacity, i.e. achieved self-healing in less than 2 h, with a healing efficiency of 95.6%. Moreover, it presented shape memory, with a complete shape memory time less than 5 min.